2018
DOI: 10.3390/rs10030440
|View full text |Cite
|
Sign up to set email alerts
|

Urban Heat Island Analysis over the Land Use Zoning Plan of Bangkok by Means of Landsat 8 Imagery

Abstract: Surface urban heat island (SUHI) maps retrieved from spaceborne sensor data are increasingly recognized as an efficient scientific support to be considered in sustainable urban planning. By means of reflective and thermal data from Landsat 8 imagery in the time interval 2014–2016, this work deals with the SUHI pattern identification within the different land use categories of Bangkok city plan. This study first provides an overview of the SUHI phenomenon in Bangkok, then singles out the surface heating behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 36 publications
5
66
0
1
Order By: Relevance
“…For air-temperature measurements, fixed measurements are most often used. However, urban-monitoring networks are generally not dense enough to characterize the processes occurring on such a small scale [16]. Thus, mobile measurements can be used, operating by transect, though they are not continuous in time, contrary to a ground measurement network [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For air-temperature measurements, fixed measurements are most often used. However, urban-monitoring networks are generally not dense enough to characterize the processes occurring on such a small scale [16]. Thus, mobile measurements can be used, operating by transect, though they are not continuous in time, contrary to a ground measurement network [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have mainly focused on studying differences in ground temperatures as a function of land-use land cover and its evolution at the city level [16,16,20,[33][34][35], temporal trends in urban SUHI in urban areas [18,36,37], the refreshing impact of parks on their surroundings [15,38,39], the evolution of SUHI as a function of day and night [9,34,40,41], the impact of vegetation on LST at the urban scale [12,36,37,42], comparison of surface temperatures and air temperature [8][9][10]20,43,44], the impact of surface temperatures on health [30,41] and transversely at surface temperatures at moderate resolutions (MODIS 1 km) [16,20,[34][35][36]42,45] but, to our knowledge, there are no similar studies such as ours that analyze the thermal monitoring of site redevelopment at such a detailed spatial and temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The LST of study area retrieved, using Landsat 8 Band10, based on the Radiative Transfer Equation (RTE) algorithm(Garcí a-Santos et al, 2018; Voogt and Oke, 2003). The advantage of this algorithm is not only it needs less amount of parameters to retrieve LST comparing with other algorithm, such as monowindow algorithm and split-window algorithm, but also it was demonstrated that it has a high LST retrieve accuracy using Band10 of Landsat 8 than split window algorithm and single channel method (Darge et al, 2019;Keeratikasikorn and Bonafoni, 2018;Shirani-bidabadi et al, 2019;Xiaolei Yu, 2014). In the status of data pre-processing, The landsat 8 thermal band 10 have been converted to at-sensor radiance at the top-of-atmosphere ( ), next, Planck's radiance function was utilized to calculating brightness temperature.…”
Section: Lst Retrieval and Validationmentioning
confidence: 99%
“…According to previous studies, UTE variation and distribution closely related to land use types, urban structure, urban surface feature materials even the air speed and cloud cover (Zullo et al, 2019). The influence factors of UTE have been extensively studied in recently years, especially the land covers, such as build-up area, water and vegetable, which were demonstrated closely related with UTE (Guo et al, 2019;Keeratikasikorn and Bonafoni, 2018;Madanian et al, 2018). However, the study of spatial distribution, heterogeneity and pattern of urban thermal environment was less researched than the former, which also is a significant research topic for sustainability development of urban environment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation